2011
DOI: 10.1007/s13143-011-0002-2
|View full text |Cite
|
Sign up to set email alerts
|

Fog detection using geostationary satellite data: Temporally continuous algorithm

Abstract: A fog detection algorithm that uses geostationary satellite data has been developed and tested. This algorithm focuses on continuous fog detection since temporal discontinuities, especially at dawn and dusk, are a major problem with current fog detection algorithms that use satellite imagery data. This is because the spectral radiance at 3.7 µm contains overlapping emissive and reflectance components. In order to determine the radiance at 3.7 µm under fog conditions, radiative transfer model simulations were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…Fog is commonly perceived as a hazardous weather situation that can impact traffic systems as well as the economy (Cermak and Knutti, 2009;Egli et al, 2018). In arid environments like the Namib desert, fog can act as a critical source of water that enables life for diverse species and helps to sustain ecosystems (e.g., Seely, 1979;Shanyengana, 2002;Ebner et al, 2011;Azúa-Bustos et al, 2011;Roth-Nebelsick et al, 2012;Eckardt et al, 2013;McHugh et al, 2015). As such, knowledge on the exact occurrence and spatiotemporal patterns of fog holds potential, ranging from socioeconomic benefits to a better understanding of fog processes and fogdriven ecosystems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fog is commonly perceived as a hazardous weather situation that can impact traffic systems as well as the economy (Cermak and Knutti, 2009;Egli et al, 2018). In arid environments like the Namib desert, fog can act as a critical source of water that enables life for diverse species and helps to sustain ecosystems (e.g., Seely, 1979;Shanyengana, 2002;Ebner et al, 2011;Azúa-Bustos et al, 2011;Roth-Nebelsick et al, 2012;Eckardt et al, 2013;McHugh et al, 2015). As such, knowledge on the exact occurrence and spatiotemporal patterns of fog holds potential, ranging from socioeconomic benefits to a better understanding of fog processes and fogdriven ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…As previous studies (e.g., Cermak and Knutti, 2009;Lee et al, 2011;Egli et al, 2016;Nilo et al, 2018) have shown, geostationary satellites have the potential to draw a spatiotemporally coherent picture of the occurrence of fog and low clouds (FLCs). However, information on FLCs from satellites is typically inferred using separate daytime (e.g., Bendix et al, 2006;Cermak andBendix, 2008, 2011;Nilo et al, 2018) and night-time (e.g., Ellrod, 1995;Cermak and Bendix, 2007) algorithms, disrupting our view of fog development at a critical time of its life cycle, as typically, shortwave radiative heating starts the dissipation of fog shortly after sunrise (Tardif and Rasmussen, 2007;Haeffelin et al, 2010;Waersted et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…For night time fog detection, the brightness temperature difference between TIR and MIR channels is considered. The emissivity of fog in MIR channel is about 0.8-0.9 and in TIR channel it is almost 1 (Ellrod, 1995;Lee et al, 2011). Therefore TIR minus MIR is greater than 0 K over foggy region.…”
Section: Corresponding Authormentioning
confidence: 90%
“…The study gives us an idea about the association of prolonged fog episode of 2010 with western disturbances over the northern plains of India. Similar kind of study based on BTD threshold technique was done to develop an algorithm on temporally continuous fog detection (Lee et al, 2011). The study included one of the major problem associated with algorithms using satellite imagery to detect fog, i.e.…”
Section: Related Workmentioning
confidence: 99%
“…However, this method was unable to essentially improve the fog detection at the time zone, because of the SNR limitation [8]. Indeed, most of the single-satellite LSF sensing methods was inaccurate at sunrise in previous studies [26][27][28].…”
Section: Introductionmentioning
confidence: 99%